Strategi Komunikasi Pemasaran pada Cafe 1618 Space dalam Upaya Menciptakan Brand Awareness di Era New Normal - fauziah, farah dini; Abidin, Zainal; Tayo, Yanti (Peneliti.net, 2024)
This research is entitled Marketing Communication Strategy at Cafe 1618 Space in an Effort to Create Brand Awareness. The purpose of this study is to determine the Marketing Communication Strategy of Cafe 1618 Space in creating Brand Awareness. This study uses Integral Marketing Communication theory. The object of this research is 1618 which is located on Jl. Panatayuda No. 54A Nagasari, Kec. West Karawang. Data collection techniques through observation, interviews and documentation. The results of this study can be concluded that the most effective marketing communication carried out by cafe 1618 Space is sales promotion, namely giving discounts and vouchers that aim to attract customer interest. In addition to the most effective sales promotion, namely advertising, it also influences the marketing communication strategy for cafe 1618 Space, namely by publishing content on Instagram social media. Keywords: Marketing Communication, Brand Awareness, Cafe